KAJIAN BIMBINGAN DAN KONSELING: KUALITAS HUBUNGAN SUAMI-ISTRI DAN KESEHATAN MENTAL IBU RUMAH TANGGA - Khairat Hsb, Fitri Husaibatul (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
This study aims to examine the effectiveness of guidance and counseling in improving the quality of marital relationships and the mental health of housewives. The research method used is a literature study by collecting data from scientific articles and journals related to the topic being discussed. The results of the study indicate that guidance and counseling can be an effective option for improving the quality of marital relationships and the mental health of housewives. BK approaches that can be used include psychodynamic, systemic, behavioral, and humanistic approaches. However, it should also be noted that the results of guidance and counseling can vary depending on the type of approach and the counselor's competence used. This research is expected to provide useful information and input for practitioners and researchers in the field of guidance and counseling, as well as for the general public who require guidance and counseling to improve the quality of marital relationships and the mental health of housewives